Irreversible bonds for higher stability of COF materials in photocatalytic reactions - Ma, Fang; Ye, Liqun (Frontiers in Fuels, 2024)
Covalent organic frameworks (COFs), one of a multitude of advanced mainstream materials in photocatalysts, are crystalline porous materials with tunable topology and high porosity and are connected by dynamic covalent bonds. We sought to achieve efficient photocatalytic yields, making the stability of the bond energy crucial. Stable bond energy will enable our products to be more economically efficient. At present, the main photocatalysts are reversible imine bonds and other 2D COFs, but irreversibly stable COFs are seldom involved. Therefore, this review surveys the relevant literature to explore the stability of irreversible bond energy, elaborating the synthesis schemes of irreversible bonds. Irreversibly connected bonds will improve the stability and durability of our synthesized catalyst in practical applications, so we seek to explore the stability of bond energy for our practical applications. In this review, we offer a detailed summary of the irreversible bonding pattern, explore the stability of COFs, and summarize classic highly crystalline ordered semiconductor COFs with irreversible bonding methods.